Quasi‐Bound States in the Continuum with Temperature‐Tunable Q Factors and Critical Coupling Point at Brewster's Angle. Issue 5 (8th March 2021) - Wu, Bing‐Ru; Yang, Jhen‐Hong; Pankin, Pavel S.; Huang, Chih‐Hsiang; Lee, Wei; Maksimov, Dmitrii N.; Timofeev, Ivan V.; Chen, Kuo‐Ping
Abstract: Quasibound state in the continuum (quasi‐BIC) is a long‐lived state with a high quality factor (Q factor). Here quasi‐BICs in nematic liquid crystal (LC) layer embedded between a distributed Bragg reflector (DBR) and a metal layer are studied. First, a special class of true BICs between the DBR and the metal film with field localization provided by the Brewster transverse electric (TE) reflection in the DBR is experimentally demonstrated. It is demonstrated that the Q factor of the quasi‐BIC can be tuned by the LC optical axis rotation in a wide range being only restricted by metal losses. The change of coupling with the radiation channel leads to a critical coupling condition, providing a total absorption of incident light. The acquired quasi‐BIC resonance is extremely sensitive to the temperature due to the narrow nematic temperature range of the LC. The quasi‐BIC transforms to BIC at the LC‐isotropic clearing point, due to closing of the radiation channel. Abstract : It is demonstrated that the quality factor (Q factor) of the quasibound state in the continuum (quasi‐BIC) can be tuned by the liquid crystal optical axis rotation in a wide range. More interestingly, the change of coupling with the radiation channel leads to a critical coupling condition and the acquired quasi‐BIC resonance is extremely sensitive to the temperature.